2022
DOI: 10.1097/mcc.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Update on Staphylococcus aureus bacteraemia

Abstract: Purpose of reviewTo review recently published evidence relevant to Staphylococcus aureus bacteremia (SAB).Recent findingsStaphylococcus aureus is the most common pathogen causing co-infections and superinfections in patients with COVID-19. Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia ratios have sharply risen during the pandemic. SAB mortality is 18% at 1 month and 27% at 3 months but has gradually decreased over the last 30 years. Recurrences and reinfections are common (9%). Standardised ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The most frequent infections are local infections, which become bacteremia when staphylococci invade into the bloodstream and colonize to cause BSI. [11] Staphylococci have a great ability to infect human hosts by adherence, invasion, persistence and evasion of the host immunity. [12] S argenteus is a novel and emerging species that is part of the S aureus complex.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent infections are local infections, which become bacteremia when staphylococci invade into the bloodstream and colonize to cause BSI. [11] Staphylococci have a great ability to infect human hosts by adherence, invasion, persistence and evasion of the host immunity. [12] S argenteus is a novel and emerging species that is part of the S aureus complex.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in rate of primary BSI among those with BSIs present on admission versus ICU-onset BSIs was not reported [8 & ]. Although Staphylococcus aureus is recognized to be an important cause of primary BSI due to its propensity to cause complicated infections [17], there is a paucity of contemporary studies that have specifically examined the influence on infecting species among primary BSI in the critically ill. In a single center cohort of 104 critically ill patients, Singh et al…”
Section: Epidemiologymentioning
confidence: 99%
“…Although Staphylococcus aureus is recognized to be an important cause of primary BSI due to its propensity to cause complicated infections [17], there is a paucity of contemporary studies that have specifically examined the influence on infecting species among primary BSI in the critically ill. In a single center cohort of 104 critically ill patients, Singh et al [9] identified central line insertion, diabetes mellitus and higher APACHE-II scores as risk factors for Gram-positive cocci BSI.…”
Section: Epidemiologymentioning
confidence: 99%
“…[ 6,7 ] MRSA can enter the body through wounds or infected invasive medical devices, resulting in secondary symptoms of infection such as pneumonia, surgical site infections, and bacteremia. [ 8 ] Without timely diagnosis and treatment, bacteremia caused by MRSA infection may lead to sudden death. [ 9 ] Therefore, in addition to good hygiene practices and appropriate epidemiological surveillance systems, the rapid and accurate detection of MDR bacteria in the early stages of infection plays a crucial role in effectively preventing the worsening of infection and community transmission.…”
Section: Introductionmentioning
confidence: 99%